THE INFLUENCE OF EDUCATIONAL VIDEOS ON EARLY PREVENTION OF STROKE AGAINST STROKE RISK IN THE ELDERLY - Yardes, Nelly; Iriana, Pramita; Riyanti, Eska; Pangastuti, Tri Endah; Resnayanti, Yeti; Silviani, Nadhia Elsa (Jurnal Keperawatan, 2025)
Every year, 15 million people worldwide have a stroke. Education using video that are thought to be simple for the elderly to grasp can alter knowledge, attitudes, and behavior among the elderly who are at risk of stroke. This study were conducted to assess the impact of early stroke preventive education videos on stroke risk in the elderly. The method was a quasi-experimental using a non-randomized pretest-posttest control group design. This study was carried out by delivering an educational video intervention for early stroke prevention for three months and comparing the results to those of the control group or without the intervention. The population of this study was the elderly, with a sampling approach of purposive sampling and a sample size of 60 people at Posbindu in the Cipayung district. The data analysis test employed was univariate and bivariate, utilizing independent t-test to assess the effect of the instructional video intervention on early stroke prevention. The difference in the average score of knowledge (1.333; pvalue = 0.011), attitude (1.533; pvalue = 0.011), and behavior (0.466; pvalue = 0.028) in the intervention group before and after the intervention was greater than the difference in the average score of knowledge (0.233; pvalue = 0.165), attitude (0.166; pvalue = 0.484), and behavior (0.000; pvalue = 1.000) in the control group. Furthermore, the independent T-test revealed that the instructional video intervention was helpful in improving knowledge (p-value = 0.064) and attitude (p-value = 0.008). Early stroke prevention education movies improve the elderly's knowledge and attitudes.